2023
DOI: 10.1111/josi.12577
|View full text |Cite
|
Sign up to set email alerts
|

Black motherhood and the dual pandemics: The protective role of stable income on mental wellbeing

Abstract: The dual pandemic (racial discrimination and COVID‐19) has contributed to mental health disparities across various social identities. Black mothers, in particular, have shouldered the heightened stresses of being Black and female during a time of immense anti‐Black racism and societal pressures to assume caretaking roles at the expense of, or in addition to, other financial obligations. Thus, this study examines the relationship between COVID‐19 related financial difficulties, racial discrimination, and the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…(2023), and Ibekwe‐Okafor et al. (2023) have also confirmed the COVID‐19 context. Similarly, previous feminist literature has documented that women have less access to key assets for survival, both before and after disaster strikes (Enarson, 2006).…”
Section: Bridging Disaster Analyses: Theorizing Racialized Disaster P...mentioning
confidence: 73%
See 1 more Smart Citation
“…(2023), and Ibekwe‐Okafor et al. (2023) have also confirmed the COVID‐19 context. Similarly, previous feminist literature has documented that women have less access to key assets for survival, both before and after disaster strikes (Enarson, 2006).…”
Section: Bridging Disaster Analyses: Theorizing Racialized Disaster P...mentioning
confidence: 73%
“…More specifically, for nearly three decades, feminist social scientists have documented the ways in which women's double burden of reproductive and productive labor compounds their disaster risks, including their risks of even greater burdens of care work, and also elevated and disproportionate risks of unemployment following a disaster (Chew & Ramdas, 2005; see also Dinella & Fulcher, 2023). Indicative of the orientation in feminist disaster studies, pathbreaking scholar of gender and disaster, Elaine Enarson argues that women are not inevitably vulnerable, but the extent of the gendered division of labor in societies puts women at particular risk (Enarson, 2006), a pattern that Garland McKinney and Meinersmann (2023), Hassoun Ayoub et al (2023), and Ibekwe-Okafor et al (2023 have also confirmed the COVID-19 context. Similarly, previous feminist literature has documented that women have less access to key assets for survival, both before and after disaster strikes (Enarson, 2006).…”
Section: Bridging Disaster Analyses: Theorizing Racialized Disaster P...mentioning
confidence: 99%
“…Neighborhood social disorder typically describes the perception or observation of social aspects of a neighborhood that signal a failure of social control (Jaśkiewicz & Wiwatowska, 2018). Social disorder is typically characterized by public behaviors such as drinking, drug use, and fighting (Jaśkiewicz & Wiwatowska, 2018; Raudenbush & Sampson, 1999; Sampson & Raudenbush, 2004; Skogan, 2012, 2015). Neighborhood poverty, individual low income, the concentration of racial and ethnic minorities, and crime rates, among others, increase the perception of neighborhood social disorder (Franzini et al., 2008; Latkin et al., 2009; Sampson & Raudenbush, 2004; Wickes et al., 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recently, empirical research has been published related to the disproportionate impacts of COVID-19 and its inequalities associated with changes in employment and income, race and ethnicity, gender, parenting, and neighborhood characteristics (Ayoub et al, 2023;Dawson et al, 2022;Fulcher & Dinella, 2022;Garland McKinney et al, 2022;Geyton & Johnson, 2022;Jiwani et al, 2022;Rehbein et al, 2022;Versey, 2022). Additionally, research has more recently been published concentrating on uniquely vulnerable populations such as women, minorities, low socioeconomic households, and the justice-involved community (Ayoub et al, 2022;Babbar et al, 2023;Dawson et al, 2022;Fulcher & Dinella, 2022;Garland McKinney et al, 2022;Geyton & Johnson, 2022;Heiman et al, 2022;Ibekwe-Okafor et al, 2022;Jiwani et al, 2022;Lipp & Johnson, 2022;Rehbein et al, 2022;Versey, 2022). The present study aims to expand on the current body of literature and understand how neighborhood disorder exacerbates the socioeconomic impacts of the COVID-19 pandemic, such as employment, housing, and access to basic necessities, particularly while taking into consideration populations especially vulnerable to socioeconomic impacts of the COVID-19 pandemic: mothers, particularly mothers with justice-involved sons, women of color, and women of low socioeconomic status.…”
Section: Justice-involved Mothers: Direct Socioeconomic Impacts Of Co...mentioning
confidence: 99%
“…While gender disparities have been examined in India, less attention has been paid in the social science literature on disparities experienced by women living at the intersection of gender and other marginalized socio‐cultural identities. Overlapping marginalized identities have the potential to create disparate outcomes that are greater than the sum of those identities (Crenshaw, 1991), and studies in other contexts such as the United States have found that women with multiple minority identities experience worse health (Garland McKinney et al., 2023; Le & Nguyen, 2021; Rushovich et al., 2021) and socioeconomic (Ibekwe‐Okafor et al., 2023; Modarressy‐Tehrani, 2020) outcomes. In India, caste membership has been found to be a critical determinant of inequity across the lifespan (Human Rights Watch, 2001).…”
Section: Introductionmentioning
confidence: 99%